Strategies and technologies for enhancing rapeseed-mustard production and farmer income - Sharma, Pankaj; Sharma, Hari Om; Rai, P. K. (Indian Farming, 2018)
As policy measures to attract thefarmers towards oilseeds, in general,and rapeseed-mustard in particularly,favourable support price, higher tariffrate on import of edible oil andeffective market intervention wouldhave to be looked. Bee-keeping inrapeseed-mustard crop can increasethe yield by 15 to 20% and willgenerate additional income tofarmers. Conduction of more numberof on different production andprotection aspects for effectivedissemination of technology isneeded.